The Philosophy of Scenography in The Amarna Period - عمر المعتز بالله محمود بسيوني (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
The research investigates the roots of scenography in ancient Egypt, especially in the era of King Akhenaten, in the 18th Dynasty in the new kingdom, specifically in his capital, Akht-Aten, in Upper Egypt. Dealing with the use of scenography in the absence of the term at this time, to consolidate the content of the Athenian religion in Egypt at that time.The ancient Egyptian artist was not only thinking about the construction of his timeless buildings to emphasize his strength and prestige, or the status of his old religion. His great civilization was not the result of a mere and or his absolute creativity of the arts of that period. But it was based on philosophical rules that were formulated by the art of scenography as a comprehensive science for the use of the arts in landscape; according to a preconceived idea and planning stemming from the potential of his religious faith. Thus, included scenography in his era as an adaptation of spatial nature and the exploitation of astronomy and the movement of the sun, to build his architecture, which decorated with drawings and lively scenes - whether religious or daily-life architecture - and to the design and implementation of fashion of this era for the people who lived in these places and their accessories and tools as well; preceding any civilization in the usage of the scenography before they started applying the idea on performing arts such as theater and cinema.